CEO compensation in Korea: Is it different than in the US? A comparison between Korean non-life insurance firms and US property-liability insurance firms - Sangyong Han; Hyejeong Mun (International Journal of Financial Studies, 2021)
This study investigates the level, structure, and pay-for-performance relationship of CEO compensation in Korean non-life insurance companies. We find that seniority plays an important role in setting CEO compensation practices and that performance-based pay, such as bonus, is more effective than base salary in enhancing shareholder value for Korean non-life insurers. Unlike previous studies that show that international differences in executive pay have been diminished considerably since the 2000s, our evidence shows that there is a remarkable difference in CEO compensation between Korean non-life insurers and U.S. property-liability insurers. Furthermore, we provide evidence that the pay-performance relationship is weaker in Korean non-life insurance companies relative to US counterparts, suggesting that it is necessary for Korean non-life insurers to tie performance-based compensation more closely to shareholder value in the design of CEO compensation.
Keywords: G22; G39; J33; 330; CEO compensation; pay-performance sensitivity; property-liability insurers